Separation and Detection of meta‐ and ortho‐Substituted Benzene Isomers by Using a Water‐Soluble Pillar[5]arene. Issue 6 (10th June 2020) - Zhang, Gengwu; Moosa, Basem; Chen, Aiping; Khashab, Niveen M.
Abstract: Efficient and energy‐saving separation of benzene isomers bearing a diverse range of functional groups is a great challenge due to their overlapping physicochemical properties. Here, we report the successfully use of a water‐soluble pillar[5]arene (WP5) as a multifunctional material for the separation and detection of meta / ortho ‐substituted benzene isomers in water. A liquid‐liquid extraction strategy was used for the separation of these benzene isomers based on their different affinity for WP5 in water. The selectivities for the meta over the ortho isomer for xylenes, chlorotoluene, and bromotoluene was 88.6 %, 88.3 %, and 95.0 % respectively, in one extraction cycle. Furthermore, a fluorescence indicator system based on WP5 and a fluorescent dye molecule (10‐methylacridinium, D) was adopted and exhibited significant fluorescence and optical discrimination upon the addition of meta ‐ compared to ortho ‐xylene, which implies that a simple "turn‐on" detection can be performed prior to engaging in the separation process. Abstract : Efficient extraction : A water‐soluble pillar[5]arene (WP5) was used for the separation of meta / ortho ‐substituted benzene isomers under ambient conditions with over 88 % selectivity for the meta isomer. Furthermore, a fluorescence indicator system based on WP5 and a fluorescent dye molecule (10‐methylacridinium, D) showed significant fluorescence and optical discrimination between the meta / ortho isomers, which implies that a simple "turn‐on" detection can be performed prior to engaging in the separation process.